Analisis Kinerja Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kota Metro - Yulita Zanaria; Aris Sunyoto (Jurnal Bisnis Darmajaya, 2018)
The purpose of this study is to describe the performance of the Metro City Asset Financial Management Agency (BPKAD) in  managing  regional  assets.  As  the  Regional  General  Treasurer,  BKAD  is  a  technical  service  that is  responsible  for receiving regional income and issuing money for regional needs through regional general cash. With the regional treasury, a region  can  manage  the  availability  of  sufficient  funds  to  finance  regional  expenditures.  In  the  regional  general cash,  it  can also be seen how much wealth a region has. Regional cash itself is contained in the comparative balance sheet which is part of the financial statements. The results of the research in cash management have received regional income and disbursed funds used  for  regional  expenditure purposes.  The  procedure  for cash  receipts  and disbursement  of  funds  directly handled  by  the regional  cash  management  section  is  regulated  in  the  guidelines  for  managing  the  business  implementation  of  the  Metro City  APND  and  so  far  the  cash  management  section  has  carried  out  its  duties  in  accordance  with  these  guidelines.  In general, Metro City BPKAD's performance in managing lancer beum assets is said to be good and still not optimal, this can be seen based on indicators used in BPKAD's performance appraisal in managing transparent assets, namely accountability, transparency, economy, efficiency and effectiveness. regional income that goes into regional treasury has increased.Keywords-Performance